2019
DOI: 10.1016/j.molcel.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

C1QBP Promotes Homologous Recombination by Stabilizing MRE11 and Controlling the Assembly and Activation of MRE11/RAD50/NBS1 Complex

Abstract: Highlights d C1QBP stabilizes the MRE11 protein by forming the MRC complex with MRE11/RAD50 d C1QBP inhibits MRE11 exonuclease activity by preventing its binding to DNA d Appropriate C1QBP levels are essential for genomic stability and DNA repair

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 67 publications
(91 reference statements)
4
38
0
Order By: Relevance
“…ATR was included in the screen a positive control for essential genes since its deletion is lethal is several cell lines due to its role in replication and the DNA damage response (Cimprich and Cortez, 2008; Flynn and Zou, 2011). Interestingly, C1QBP, a complement gene which was recently shown to play a role in the DNA damage response by modulating DNA resection, was essential in a number of cell lines, further validating our screening approach (Bai et al, 2019)( Figure 1A ) (Supplementary Table 1) .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…ATR was included in the screen a positive control for essential genes since its deletion is lethal is several cell lines due to its role in replication and the DNA damage response (Cimprich and Cortez, 2008; Flynn and Zou, 2011). Interestingly, C1QBP, a complement gene which was recently shown to play a role in the DNA damage response by modulating DNA resection, was essential in a number of cell lines, further validating our screening approach (Bai et al, 2019)( Figure 1A ) (Supplementary Table 1) .…”
Section: Resultssupporting
confidence: 72%
“…C5aR1 is the most advanced complement target in the oncology space with preclinical and clinical trial efforts mainly focused on blocking C5aR1 to improve anti-tumor immunity (Ajona et al, 2017; Markiewski et al, 2008; Massard et al, 2019; Wang et al, 2016). However, given the recently discovered autocrine and intracellular cancer-cell intrinsic roles of complement system proteins, it is important to also investigate the contribution of these functions to tumor responses (Bai et al, 2019; Block et al, 2019; Cho et al, 2014; Olcina et al, 2020). The discovery of cancer cell intrinsic functions that can potentiate anti-tumor responses without having to rely on increased T-cell infiltration would be particularly beneficial, especially in the context of so-called “cold” tumors (Duan et al, 2020; Roumenina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Conditional inactivation of MRE11 in germ cells can be performed in future to examine this possibility. C1QBP, a recently identified binding partner of MRE11 and RAD50, might mediate the residual MRE11 activity on meiotic chromosomes in the absence of NBS1 [57]. Besides being important for repairing SPO11-linked DSBs, the NBS1 ortholog XRS2 in yeast is also required for the formation of meiotic SPO11-linked DSBs [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, no associations between these two pathways and how they may cooperate to regulate apoptosis have been suggested in a cancer context, which likely reflects the fact that intracellular roles for complement proteins have only recently been considered (Liszewski et al, 2013;Arbore et al, 2017;Elvington et al, 2017;Kremlitzka et al, 2019). Of note, a recent study reported that complement factor properdin may act as a tumor suppressor in breast cancer models by upregulating ER-activated pro-apoptotic transcription factor DDIT3 (Block et al, 2019 (Bai et al, 2019). These studies, like ours, highlight the importance of investigating intracellular functions of complement proteins.…”
Section: Discussionmentioning
confidence: 99%